Identifying Unique Coding Strategies Between Mossy Fibre and Interneuron Synapses - Ma, Yishan (Université d'Ottawa / University of Ottawa, 2024)
Animals use spatial navigation to move about their environment and the hippocampus is the centre of processing of spatial information. We want to understand how the mossy fibre (MF) of the hippocampus (HPC) decodes inputs from the entorhinal cortex (EC) and contributes to spatial memory processing. MF terminals have unique anatomical features that connect dentate gyrus granule cells (DG; DGGC) to CA3 pyramidal cells (CA3PC), along with single release site extensions that synapse onto CA3 stratum lucidum interneurons (SLIN). Using whole-cell patch-clamp electrophysiology, we recorded from MF-CA3PC synapses and stimulated patterns that differed in frequency, but the number of stimuli remained the same. We discovered a novel coding strategy, termed AP Counting. AP Counting happens when the synapse responds to the number of stimuli, irrespective of their frequencies. It remains unknown whether this is a uniform feature of presynaptic elements or of various postsynaptic elements. Therefore, is the same coding strategy, AP Counting, preserved between MF-SLINs? Preliminary findings revealed that MF-SLIN coding strategies to be different from the ones employed at MF-CA3PCs. Thereby, we separated the three populations by coding strategy and named them SLIN population 1 (SLIN1), SLIN population 2 (SLIN2) and SLIN population 3 (SLIN3). SLIN1 and SLIN3 employed a rate coding strategy, while SLIN2 was insensitive to different frequencies. In conclusion, MF-SLINs utilise distinct coding from MF-CA3PCs, namely, rate coding, and frequency insensitivity. These two different ways of processing (EC) contribute to the complexity of the neural dynamics of the DG-CA3 network. In order to understand the greater impact of these two types of synapses, we would use computational modelling to study the dynamics of the DG-CA3 network.
Keywords: CA3; DG; stratum lucidum interneurons; SLIN; hippocampus; spatial navigation; DG-CA3 dynamics; coding